Effects of endurance training on the isocapnic buffering and hypocapnic hyperventilation phases in professional cyclists. Issue 6 (1st December 2000) - Chicharro, José L; Hoyos, Jesús; Lucía, Alejandro
Abstract : Objectives —To evaluate the changes produced in both the isocapnic buffering and hypocapnic hyperventilation (HHV) phases of professional cyclists (n = 11) in response to endurance training, and to compare the results with those of amateur cyclists (n = 11). Methods —Each professional cyclist performed three laboratory exercise tests to exhaustion during the active rest (autumn: November), precompetition (winter: January), and competition (spring: May) periods of the sports season. Amateur cyclists only performed one exercise test during the competition period. The isocapnic buffering and HHV ranges were calculated during each test and defined as Vo 2 and power output (W). Results —No significant differences were found in the isocapnic buffering range in each of the periods of the sports season in professional cyclists. In contrast, there was a significant reduction in the HHV range (expressed in W) during both the competition (p<0.01) and precompetition(p<0.05) periods compared with the rest period. On the other hand, a longer HHV range (p<0.01) was observed in amateur cyclists than in professional cyclists (whether this was expressed in terms of Vo 2 or W). Conclusions —No change is observed in the isocapnic buffering range of professional cyclists throughout a sports season despite a considerable increase in training loads and a significant reduction in HHV range expressed in terms of power output.